The stay interview : a manager's guide to keeping the best and brightest - Finnegan, Richard P. (AMACOM American Management Association, 2015)
It's the worst sort of surprise: A valued and seemingly happy employee gives his notice. Can you do anything at this point Probably not. Could you have anticipated the departure and tried to prevent it? Absolutely. That's where this book comes in. This practical guide introduces managers to a powerful new engagement and retention tool: the stay interview. Smart companies have begun conducting these periodic reviews in order to discover why their important talent might leave and to solve any problems before they actually quit. The Stay Interview shows managers how to: Prepare for the meeting An.